REBT MENGATASI NEGATIVE THINKING PADA ANAK BROKEN HOME - Fatimah Setiani; Agus Heriyanto; Nurfitriyanti Nurfitriyanti (STKIP MUHAMMADIYAH SAMPIT, 2019)
Without realizing it in our daily lives, a child who experiences a broken home has negative thoughts. This study was to determine the effectiveness of the Rational Emotive Behavior Therapy approach in Overcoming Negative Thinking in Broken Home Children. This study uses descriptive phenomenological qualitative research with a case study approach, data collection using interviews, observations and problem check list models. The final results of the process of implementing individual counseling in this study are considered to be quite effective with a percentage of 40%. These results can be seen from the change in negative thinking from the subject which gradually diminishe.